Instrumental technology of dùndún drum of the Yoruba (2009)
This paper is a documentation of the systematic process of constructing dundun - the most common drum in Yorubaland. Using interview and participant-' observer methods, a collection of data through the aid of audio tape recorder and digital/still camera was embarked upon during a fieldwork carried out in Ilora, Oyo state. After examining the numerous stages in the design and construction of the dundun, the paper went on to describe its playing position. It also stressed the cruciality of providing incontrovertible evidences to challenge the continuous reliance on Western European concepts in the teaching of courses on instrumental technology at the expense of authentic indigenous knowledge systems found in African continent. Finally, the paper posited that the time is ripe for African musicologists to engage in meaningful researches into various aspects of African traditional musical instruments including their technology with a view to documenting, preserving and promoting the rich and invaluable indigenous knowledge systems of Africa.